It looks like it goes through (0,-3) and (1,2), so the gradient is (change in y)/(change in x) ->
(-3-2)/(0-1) = 5
So y=5x+b
Then as we know it passes the y axis at (0,-3) so b= -3
So we have y=5x-3
Answer:
74 and 740
Step-by-step explanation:
Answer:
D.
Step-by-step explanation:
(4 x 8) + (4 x 3)=44
4 x (8 + 3)=44
X is the number of movies for the cost of the plan to be the same.
4.25x=36+3.5x
4.25x-3.5=36
0.75x=36
x=36/0.75
x=48
Parent Function: f(x)=x^2
Horizontal Shift: Right 5 Units
Vertical Shift: Up 3 Units
Reflection about the x-axis: None
Reflection about the y-axis: None
Vertical Compression or Stretch: None